Innovative Approach to the University Intellectual Capital Management - G. M. Sundukova (Управление)
The article deals with the innovative approach to the management of the intellectual capital of the university, taking into account the specifics of the educational institutions. It is concluded that the formation of the intellectual capital of the university is based on the process approach and intellectual capital growth software requires a strategic approach.